The correlation between neutrophil/lymphocyte ratio and the MRI burden and cognitive function in patients with cerebral small vessel disease - Zhao, Mengyao; Xie, Xiaohua; Hao, Zhiwei; Ren, Mengsi; Teng, Zhenjie; Xu, Jing; Shan, Chunhui; Dong, Yanhong; Lv, Peiyuan (Frontiers in Neurology, 2025)
ObjectiveAims to explore the relationship between neutrophil/lymphocyte ratio (NLR) and the total burden of imaging markers and cognitive function in patients with cerebral small vessel disease (CSVD).MethodsA retrospective study was conducted on 148 hospitalized CSVD patients at Hebei General Hospital from January 2022 to September 2024, with complete clinical and laboratory data. NLR was calculated as neutrophil count/lymphocyte count. According to the Mini-Mental State Examination (MMSE) score, patients were divided into a cognitive impairment group (n = 89) and a non-cognitive impairment group (n = 59). The total CSVD burden was assessed based on magnetic resonance imaging (MRI). We used logistic regression models, restricted cubic spline plots, Spearman correlation, and mediation analysis to evaluate the relationship between NLR in CSVD patients and CSVD burden and cognitive impairment.ResultsThe results of the multivariate logistic regression showed that after adjusting for all potential confounding factors, an elevated NLR in CSVD patients was significantly associated with the risk of cognitive impairment (OR: 3.263; 95% CI: 1.577 to 6.752; p = 0.001) and severe CSVD burden (OR = 2.246, 95% CI: 1.346 ~ 3.750, p = 0.002). The restricted cubic spline plot shows that after adjusting for confounding factors, the NLR level is linearly associated with the risk of CI (P for total = 0.022, P for non-linear = 0.231) and the total burden of CSVD (P for total = 0.005, P for non-linear = 0.448). Correlation analysis shows that NLR is positively correlated with the CSVD score (rs = 0.246, p = 0.003). Furthermore, the results of the mediation analysis indicate that after adjusting for confounding factors, the burden of CSVD has a significant mediating effect on the relationship between NLR levels and cognitive impairment (ab = 0.028, 95% CI: 0.004 to 0.070, p = 0.012); 20.9% of the total effect of NLR on cognitive impairment in CSVD patients can be attributed to the presence of CSVD burden.ConclusionElevated NLR in CSVD patients is associated with the burden of CSVD and cognitive impairment. The mediating role of CSVD burden suggests that elevated NLR may lead to cognitive impairment by exacerbating the burden of CSVD.